Event characteristics of intra-seasonal climate circulations - Tennant, Warren James (Not Specified, 2023)
An analysis of rainfall characteristics over the summer rainfall areas of South Africa is done in order to find links between rainfall variability and the general circulation. Seasonal rainfall totals are clearly linked to significant rain days, indicating the importance of evaluating synoptic-scale event characteristics. Rank ordered rainfall characteristics reveal that normal rainfall may be considered as the middle three quintiles, with the outer quintiles representing wet and dry conditions. The general circulation in tenns of atmospheric state (humidity and temperature), moisture and heat transport, and energy exchange - with attention to tropical-extratropical cloud-bands, are central to wet seasons in South Africa. These are generally associated with deep convection that is driven by vertical instability. Transport of moisture into South Africa generally takes place from the east with the Indian Ocean being a major source of water vapour. Although important, fluctuations in moisture transport are not clearly associated with rainfall. This is because moisture is a necessary but not a sufficient condition for rainfall. Atmospheric dynamics producing rainfall are a combination of disturbances of mid-latitude and tropical origin. These disturbances often initiate the tropical-temperate cloud-band where eddy available potential energy, generated through surface heating over land, is converted to eddy kinetic energy. It is generally mid-latitude disturbances with stronger vertical shear that are associated with rainfall events. Increased baroclinic activity in the Southern Ocean south of South Africa, as such, is generally associated with dry seasons. During these seasons there is usually a greater amount of available potential energy which strengthens the southern branch of the Hadley Cell. The effect of this is to increase the strength of the subtropical jet through enhanced poleward flux of angular momentum. The resulting increase in baroclinicity in the South Atlantic Ocean then disrupts rainfall over South Africa through the advection of dry air from the west by the vertical-mean wind component. General circulation models are shown to capture inter-annual variability such that forecasts of regional rainfall, of useful skill at a seasonal scale, may be made. However, the skill level with regard to daily circulation, restricts their use to the large-scale circulation. Nonetheless, the analysis of rainfall and the links to large-scale circulation, discussed in the thesis, provide information to produce more skilful seasonal forecasts without having to model small-scale features directly. Such forecasts may also include additional information on rainfall characteristics, such as number of rain-days and length of dry spells.